Drought analysis in Al-Hassaka and Al-Qamshli during the period 1957-2012 using modified rainfall anomaly index - سكاف, ميشيل; بركات, راما (Latakia University Journal -Biological Sciences Series, 2020)
Drought is one of the most adverse meteorological phenomenon affecting water resources, agricultural production and natural ecosystems. Monthly rainfall data for two meteorological station (Al-Hassaka and Al-Qamshli) located in Syrian Aljazeera region were used to identify spatiotemporal characteristics of drought during the period 1957-2012 in this region which classified as the most important for cereals crops production. Modified rainfall anomaly index was applied to evaluate drought intensity and frequency at seasonal and annual time scale. Trends with mann-kendall test and point change analysis were used to detect changes in drought intensity and determine years of change. Scattergram with descriptive analysis were utilize for two period 1958-1985 and 1985-2012 to estimate changes in drought frequency. Results showed a significant changes in drought intensity during rainy season in both stations related to decreasing tendency in drought index values in spring (-0.94 , -1.33) and winter (-0.93 , -0.86) in Al-Hassaka and Al-Qamshli respectively. Distinct shift to more intense and frequent droughts was observed since 1998-1999. This changes well pose big challenges for water resources management, stability of agricultural production and rangelands exploitation and restoration.